2015
DOI: 10.1136/bmj.h117
|View full text |Cite
|
Sign up to set email alerts
|

Association between randomised trial evidence and global burden of disease: cross sectional study (Epidemiological Study of Randomized Trials--ESORT)

Abstract: Objectives To determine whether an association exists between the number of published randomised controlled trials and the global burden of disease, whether certain diseases are under-investigated relative to their burden, and whether the relation between the output of randomised trials and global burden of disease can be explained by the relative disease burden in high and low income regions. Design Cross sectional investigation. Study sample All prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 15 publications
(22 reference statements)
3
34
0
1
Order By: Relevance
“…DALYs and other health-gap metrics are one of many potential inputs when setting health policy and investment priorities, but major research organisations and funders such as the US National Institutes of Health and others note the use of DALYs to inform budgeting decisions 43, 44, 45, 46. Beyond health metrics, many other inputs are required for decision making, ranging from the effectiveness of different adoptable policies and programmes, to key social, cultural, and ethical considerations.…”
Section: Discussionmentioning
confidence: 99%
“…DALYs and other health-gap metrics are one of many potential inputs when setting health policy and investment priorities, but major research organisations and funders such as the US National Institutes of Health and others note the use of DALYs to inform budgeting decisions 43, 44, 45, 46. Beyond health metrics, many other inputs are required for decision making, ranging from the effectiveness of different adoptable policies and programmes, to key social, cultural, and ethical considerations.…”
Section: Discussionmentioning
confidence: 99%
“…This is all the more necessary as in 2015, an analysis of randomized clinical trials in the Clinicaltrials.gov database confirmed that there was a weak association existing between global burden of disease and number of published randomized trials [20].…”
Section: Discussionmentioning
confidence: 89%
“…Attempts to provide recommendations for rarely encountered scenarios, attracting few if any adequately powered RCT, will also lower the rate of evidence-based recommendations. 10 So how to proceed? Using this yardstick, about 80% or more of our daily practice is supported by RCT or compelling nonrandomised evidence.…”
Section: Filling the Glass Of Evidence-based Medicinementioning
confidence: 99%
“…8 Third, the ongoing shortfall in practice-based evidence often reflects factors beyond the control of EBM: lack of equipoise among clinicians who hold strong beliefs about the effects of interventions and who will not allow their patients to be recruited into RCT; 9 and the skewing of the research agenda, in part by commercial interests, towards cardiovascular disease and cancer, ignoring equally prevalent conditions such as musculoskeletal disease and depression which impact considerably on quality of life and function. 10 So how to proceed? First, the absence in many guidelines of an explicit system for grading quality of evidence and strength of recommendations calls for wider acceptance of the Grading of Recommendations Assessment, Development and Evaluation system.…”
Section: Filling the Glass Of Evidence-based Medicinementioning
confidence: 99%